Beyond Compliance: Integrating Balinese Hindu Ethics into Ethically Embedded Internal Control within Indonesian University Governance - Aryawati, Ni Putu Ari; Triyuwono, Iwan; Roekhudin, Roekhudin; Endang Mardiati (Journal of Cultural Analysis and Social Change, 2025)
This study critically examines how Tri Kaya Parisudha, the Balinese Hindu philosophical ideas of manacika (right thought), wacika (right speech), and kayika (right action), are used in the internal control systems of religious colleges and universities. It wants to break down a governance model that is based on culture and spirituality and that deals with the limits of the traditional COSO-based internal control framework in terms of knowledge and practice. The study is based on a qualitative, postmodern framework and uses in-depth interviews, participant observation, and documentary analysis. The data is then analyzed using a modified interactive model of Miles and Huberman. The real-world results from higher education institutions governed by the Ministry of Religious Affairs in Indonesia show a change in the way internal controls are done: manacika rethinks risk assessment in terms of moral cognition; wacika changes audit communication into dialogic, non-punitive engagement; and kayika redefines control activities as proactive and value-driven actions. When these native ideas are applied to the Government Internal Control System (SPIP), they create a hybrid governance structure that combines following the rules with moral and spiritual responsibility. This study adds to the body of research on governance by suggesting a localized, ethics-based internal control model that is both theoretically sound and useful in real life. It encourages future research to look into spiritually embedded control systems as valid alternatives to hegemonic governance paradigms and moves the conversation forward on pluralistic, culturally sensitive institutional monitoring methods.